Interpretation and Perception of Slow, Moderate, and Fast Swimming Paces in Distance and Sprint Swimmers. Issue 3 (June 2014) - Invernizzi, Pietro Luigi; Longo, Stefano; Scurati, Raffaele; Maggioni, Martina A.; Michielon, Giovanni; Bosio, Andrea
This study assessed how accurately professional swimmers can interpret instructions to swim "slow, " "moderate, " and "fast." 8 distance swimmers (6 males, 2 females; M age = 19 yr., SD = 3) and 8 sprint swimmers (7 males, 1 female; M age = 18yr., SD = 1) performed an all-out 50-m crawl stroke and three sets of 8 × 50-m crawl stroke trials interpreting the coach's instruction to swim at slow, moderate, and fast paces. No differences were detected between groups in absolute speed. Nevertheless, distance and sprint swimmers significantly differed in speed normalized to their own 50-m all-out speed (effect sizes = 6.72, 6.20, 1.35 for slow, moderate, and fast, respectively), stroke frequency (effect sizes = 0.81, 1.12, 1.54, respectively), and blood lactate concentration (effect sizes = 0.99, 2.56, 1.70, respectively).